Establishment of 3D Neuro-Organoids Derived from Pig Embryonic Stem-Like Cells - Seon-Ung Hwang (International Journal of Molecular Sciences, 2021)
Although the human brain would be an ideal model for studying human neuropathology, it is difficult to perform in vitro culture of human brain cells from genetically engineered healthy or diseased brain tissue. Therefore, a suitable model for studying the molecular mechanisms responsible for neurological diseases that can appropriately mimic the human brain is needed. Somatic cell nuclear transfer (SCNT) was performed using an established porcine Yucatan EGFP cell line and whole seeding was performed using SCNT blastocysts. Two Yucatan EGFP porcine embryonic stem-like cell (pESLC) lines were established. These pESLC lines were then used to establish an in vitro neuro-organoids. Aggregates were cultured in vitro until 61 or 102 days after neural induction, neural patterning, and neural expansion. The neuro-organoids were sampled at each step and the expression of the dopaminergic neuronal marker (TH) and mature neuronal marker (MAP2) was confirmed by reverse transcription-PCR. Expression of the neural stem cell marker (PAX6), neural precursor markers (S100 and SOX2), and early neural markers (MAP2 and Nestin) were confirmed by immunofluorescence staining. In conclusion, we successfully established neuro-organoids derived from pESLCs in vitro. This protocol can be used as a tool to develop in vitro models for drug development, patient-specific chemotherapy, and human central nervous system disease studies.